Anti-Biofilm Activities from Marine Cold Adapted Bacteria Against Staphylococci and Pseudomonas aeruginosa - Papa, Rosanna; Selan, Laura; Parrilli, Ermenegilda; Tilotta, Marco; Sannino, Filomena; Feller, Georges; Tutino, Maria L.; Artini, Marco (Frontiers in Microbiology, 2015)
Microbial biofilms have great negative impacts on the world’s economy and pose serious problems to industry, public health and medicine. The interest in the development of new approaches for the prevention and treatment of bacterial adhesion and biofilm formation has increased. Since, bacterial pathogens living in biofilm induce persistent chronic infections due to the resistance to antibiotics and host immune system. A viable approach should target adhesive properties without affecting bacterial vitality in order to avoid the appearance of resistant mutants. Many bacteria secrete anti-biofilm molecules that function in regulating biofilm architecture or mediating the release of cells from it during the dispersal stage of biofilm life cycle. Cold-adapted marine bacteria represent an untapped reservoir of biodiversity able to synthesize a broad range of bioactive compounds, including anti-biofilm molecules. The anti-biofilm activity of cell-free supernatants derived from sessile and planktonic cultures of cold-adapted bacteria belonging to Pseudoalteromonas, Psychrobacter and Psychromonas species were tested against Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa strains. Reported results demonstrate that we have selected supernatants, from cold-adapted marine bacteria, containing non-biocidal agents able to destabilize biofilm matrix of all tested pathogens without killing cells. A preliminary physico-chemical characterization of supernatants was also performed, and these analyses highlighted the presence of molecules of different nature that act by inhibiting biofilm formation. Some of them are also able to impair the initial attachment of the bacterial cells to the surface, thus likely containing molecules acting as anti-biofilm surfactant molecules. The described ability of cold-adapted bacteria to produce effective anti-biofilm molecules paves the way to further characterization of the most promising molecules and to test their use in combination with conventional antibiotics.